O75: SINGLE CENTRE EXPERIENCE OF SIROLIMUS THERAPY IN HEAD AND NECK VASCULAR MALFORMATIONS. (27th April 2021) - Pang, C; Evans, N; Papadopoulou, A; Khalifa, M; Tsui, J; Hamilton, G; Lim, CS; Brookes, J
Abstract: Introduction: To assess the efficacy and safety of Sirolimus in the treatment of low-flow head and neck (H&N) vascular malformations Method: Patients who presented to our tertiary referral clinic were assessed for eligibility. Suitable patients were commenced on Sirolimus at 0.8 mg/m 2, administered orally twice daily, which was approved by our trust Drug and Therapeutic Committee. Patients were reviewed on a monthly basis for a total of six months with an additional one-month review to check for effects upon ceasing treatment. Efficacy and safety were measured through functional and radiological response, laboratory investigations and quality of life questionnaire (36-Item Short Form Health Survey (SF-36), Hospital Anxiety and Depression Scale (HADS) and Visual Analogue Score for Pain (VAS-P)). Result: Seven patients (mean age 39 years, range 23-65 years) were recruited. One patient did not complete treatment due to intolerable side effects. All patients had a partial response with no patients showing disease progression or complete response. All post-treatment MRI scans showed stable disease with five patients demonstrating a decrease in lesion volume. Five patients reported return of symptoms at one-month post review upon discontinuation of treatment. No statistical significance (P>0.05) in all eight domains of SF-36, HADS, VAS-P and radiological vascular lesion volume between pre- and post-treatment. Most common reported side effects were mouth ulcers (n=2) and metabolic/laboratory abnormality (n=2) Conclusion: Sirolimus is an effective and safe treatment for patients with complicated low-flow H&N vascular malformations. This provides an alternative treatment where interventional therapy is considered to be limited or challenging. Take-home message: Sirolimus is an effective and safe treatment option for patients with complicated low-flow head and neck vascular malformations where interventional therapy is limited or challenging.